PENGARUH EKSTRAK DAUN KEMANGI (Ocimum sanctum L.) TERHADAP MOTILITAS DAN KONSENTRASI SPERMATOZOA MENCIT JANTAN (Mus musculus) - Safwan; Taufan; Sugara; Mutiara Kusuma Rohmia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
We have conducted a research on the effect of the extract of leaves basil (Ocimum sanctum L) on male mice to investigate the consentration and motility spermatozoa mice. Twoty male mice which has age about 2 months with wight 20 - 25 g were divided into four groups. The extract was provided orally daily until the 20 th day. At 21th day were sacrificed and determine of consentration and motility. The result of the research showed that the extract of Ocimum sanctum L leaves that being given during 20 days with the dosage of 50 mg/g body weight, 100 mg/g bw, and 250 mg/g bw could signifi increase the consentration and motility spermatozoa mice.